A new species of endemic frog belonging to genus Nannophrys Günther, 1869 (Anura: Dicroglossinae) from Sri Lanka - Fernando, Samantha Suranjan; Wickramasingha, L.j. Mendis; Rodirigo, Roshan K. (Zootaxa, 2007)
The paper describes a new frog of the genus Nannophrys from Sri Lanka. The new species is distinguished from all other Nannophrys species by the following combination of morphological characters; distal subarticular tubercle and penultimate subarticular tubercles of 4th toe are well separated (vs. these two tubercles close in all other species of the genus). Supernumerary tubercle absent or smaller than penultimate subarticular tubercle on 4th toe. A hard sharp narrow symphysial knob and close pair of sharp apophyses on anterior edge of mandible and symphysial knob lower than two apophyses (vs. all other species with a blunt wider symphysial knob and wider pair of apophyes on anterior edge of mandible, and symphysial knob of same height or higher than two apophyses. Palmar tubercles comparatively smaller, inner palmar tubercle separated from outer palmar tubercle (vs. other relatives possess palmar tubercles comparatively large, inner palmar tubercle connected with outer palmar tubercle). Ecological and distributional notes for the new species are given.